2021
DOI: 10.1371/journal.pone.0255965
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective multicenter comparison of conditional cancer-specific survival between laparoscopic and open radical nephroureterectomy in locally advanced upper tract urothelial carcinoma

Abstract: Background Upper urinary tract urothelial carcinomas are relatively rare and have a cancer-specific survival rate of 20%–30%. The current gold standard treatment for nonmetastatic high-grade urinary tract urothelial carcinoma is radical nephroureterectomy with bladder cuff resection. Objective This study aimed to compare conditional cancer-specific survival between open radical nephroureterectomy and laparoscopic radical nephroureterectomy in patients with nonmetastatic stage pT3-4 or TxN(+) locally advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, the enrolled studies were published before August 2016, and a more recent meta-analysis showed comparable oncological outcomes between the two groups (7). Moreover, Kim et al analyzed the conditional CSS to minimize bias caused by inherent time data properties, and found no signi cant difference in conditional CSS between the two modalities (9). In our series, patients in the minimally invasive group had better OS and CSS than those in the open surgery group, even after adjusting for confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the enrolled studies were published before August 2016, and a more recent meta-analysis showed comparable oncological outcomes between the two groups (7). Moreover, Kim et al analyzed the conditional CSS to minimize bias caused by inherent time data properties, and found no signi cant difference in conditional CSS between the two modalities (9). In our series, patients in the minimally invasive group had better OS and CSS than those in the open surgery group, even after adjusting for confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant therapy has been shown to down-stage primary tumors at a rate of 38% in eligible patients. However, unlike urothelial carcinomas of the bladder, many studies evaluating locally advanced urothelial carcinomas of the upper tracts report primary usage of platinum-based chemotherapy or immunotherapy in the adjuvant setting [2,17 ▪ ]. One study reported that approximately 47% of patients with locally advanced urothelial carcinomas of the upper tract received chemotherapy after RNU [17 ▪ ].…”
Section: Locally Advanced Urothelial Carcinomas Of the Upper Tractmentioning
confidence: 99%
“…This study is unique as other recent studies comparing oncologic and surgical outcomes between open and minimally invasive approaches for RNU included a limited number of locally advanced upper tract tumors [20,21]. However, that study did not include patients who received neoadjuvant chemotherapy, preventing determination of the rate of downstaging by preoperative chemotherapy at the time of RNU [17 ▪ ].…”
Section: Locally Advanced Urothelial Carcinomas Of the Upper Tractmentioning
confidence: 99%
See 2 more Smart Citations